Kingdom of Netherlands : Netherlands; 2011 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Kingdom of Netherlands; Netherlands. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
In this study, the stability of the economy of the Netherlands is overviewed. Bank profitability has recovered. The housing and mortgage markets are relatively stable, although vulnerabilities to household balance sheets are rising. The results of stress tests in the context of the Financial Stability Assessment Program (FSAP) update are welcomed, which show resilience of bank capital and liquidity buffers under extreme scenarios. Executive Directors agreed that structural reforms continue to be key to lifting the Netherlands's long-term growth prospects. Further reforms of the tax and benefit systems are needed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet